2019
DOI: 10.1101/709063
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Biases in GWAS – the dog that did not bark

Abstract: Background: Genome wide association studies (GWAS) of specific diseases are central to scientific discovery. Bias from inevitably recruiting only survivors of genetic make-up and disease specific competing risk has not been comprehensively considered. Methods: We identified sources of bias using directed acyclic graphs, and tested for them in the UK Biobank GWAS by making comparisons across the survival distribution, proxied by age at recruitment. Results: Associations of genetic variants with some diseases de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 26 publications
1
7
0
Order By: Relevance
“…Accordingly, gene-set-based analysis by Open Target Post GWAS highlighted the probable pleiotropic effects of detected loci, which are likely acting as a common genetic etiology for BP and cardiovascular diseases. Accordingly, the lethal cardiovascular diseases may affect allele frequency of effective variants with advancing age in our study due to survival reduction, so overlook the effect of functional variants in older groups as a competing risk [42,43].…”
Section: Discussionmentioning
confidence: 83%
“…Accordingly, gene-set-based analysis by Open Target Post GWAS highlighted the probable pleiotropic effects of detected loci, which are likely acting as a common genetic etiology for BP and cardiovascular diseases. Accordingly, the lethal cardiovascular diseases may affect allele frequency of effective variants with advancing age in our study due to survival reduction, so overlook the effect of functional variants in older groups as a competing risk [42,43].…”
Section: Discussionmentioning
confidence: 83%
“…We also acknowledge that GWAS of associations of genetic variants on chronic diseases can be prone to selection bias from surviving competing risk. Methods to assess genetic effects on chronic diseases are needed to account for competing risk before recruitment [ 60 ].…”
Section: Discussionmentioning
confidence: 99%
“…As smoking and alcohol drinking are strongly associated with survival, we performed analyses stratified by median age at study of cases and controls (67 years) and examined whether MR estimates observed overall were consistent with those seen in younger participants in whom survival bias is unlikely as mortality rates are low in this group. [25][26][27] The consortium included prevalent and incident patients. If genetic variants have a stronger effect on survival in PD patients than controls, genetic associations may be biased.…”
Section: Statistical Analysesmentioning
confidence: 99%